Stacking sequence optimization for maximum buckling load of simply supported orthotropic plates by enhanced permutation search algorithm. Issue 10 (3rd October 2021) - Jing, Zhao; Sun, Qin; Zhang, Yongjie; Liang, Ke
Abstract : An enhanced permutation search (EPS) algorithm is proposed for stacking sequence optimization of simply supported orthotropic plates to maximize the buckling load. By taking advantage of the approximate linear superposition regular of buckling load factor and accounting for the nonlinear effects of buckling mode as well as the non-dimensional anisotropic coefficients, the stacking sequence design is decomposed to three phases. First, the best ply orientations are identified using the sequential permutation table with multiple buckling modes. Secondly, the stacking sequence is designed from the mid-plane to the outermost position sequentially within a nested-loop search accounting for the buckling mode. Thirdly, the signs of the ply orientations are designed independently to control the bending–twisting coupling effects. Numerical examples are presented to verify the robustness and efficiency of the EPS, and the results are compared with those of heuristic algorithms. Better optimal solutions are obtained by EPS, with higher efficiency.